Comparison of pig restraint, sampling methods, and analysis on blood lactate concentration - Buzzard, B.L.; Edwards-Callaway, L.N.; Anderson, D.B.; Engle, T.E.; Grandin, T.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
The objective of the study was to examine the effects of restraint and blood sampling method on blood lactate concentration (LAC) in pigs. Restraint methods used were snaring or restraint with sorting boards. Blood was sampled from 120 pigs at approximately 165 d of age (278.0 ± 6.4 lb) over 2 consecutive days. Each day, 30 pigs were sampled per method. All pigs were housed in one barn, and pigs in adjacent pens were not sampled simultaneously. Snaring consisted of a trained handler snaring each pig while blood was collected via jugular venipuncture (approximately 7 mL). Restraint with sorting boards consisted of a trained handler restraining each pig with two sorting boards and the side of the pen to form a three-sided barrier to reduce pig movement. The distal ear vein was pricked with a 20-gauge needle to obtain several drops of blood for LAC analysis. Lactate concentration was measured using a handheld lactate analyzer. The duration of restraint and a behavior score (1 to 4; 1 = no vocalization or movement and 4 = constant movement, vocalization, and struggle) for each pig were recorded during sampling. Blood lactate was compared between the 2 sampling methods and duration of restraint was used as a covariate in the analysis.
Keywords: Swine; Blood; Laboratory; Lactate; Nursery pig; Restraint; Stress